Peran Peternakan Sapi Perah dalam Sistem Agribisnis Lokal: Analisis Ketahanan Pangan dan Ekonomi Wilayah Parongpong - Daffa Surya; Muhammad Riziq; Hasan Syahroni; Andrean Wijaya; Muhammad Zelvin Pasha; Muhammad Aerosena (Journal of Economic and Business Advancement, 2026)
This study examines the role of dairy cattle farming within the local agribusiness system of Parongpong, focusing on its contribution to food security and regional economic stability. The research employs a descriptive-analytical approach based on field observations, interviews with farmers and stakeholders, and documentation of local agribusiness practices. The results indicate that dairy farming in Parongpong has developed through a long historical process and currently operates as an integrated agribusiness system linking upstream input provision, milk production, cooperative institutions, and downstream distribution. Milk production plays a dual role as a source of animal-based nutrition and as a stable source of daily income for farming households. The sector also generates significant employment opportunities, both directly and indirectly, and creates multiplier effects across supporting sectors such as feed supply, transportation, and local trade. Cooperative institutions function as key stabilizers by ensuring market access, quality control, and price stability. Overall, the findings demonstrate that dairy farming in Parongpong is not merely a primary production activity but a strategic economic and food system component that strengthens local resilience and supports sustainable regional development.